PEMANFAATAN LAHAN MATI DI GAMPONG LEUBOK TILAM KECAMATAN COT GIREK KABUPATEN ACEH UTARA DALAM TINJAUAN EKONOMI SYARIAH - Razali Razali (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2017)
Utilization of dead land or ihya'ul mawat is part of the opening of economic livelihoods of society, but many we see in the field of land is not utilized properly. The problem to be studied is how the concept of land utilization dies in the sharia economic review and how the use of dead land in gampong leubok tilam kecamatan cot girek in accordance with sharia economy. The objective is to know the concept of utilization of dead land in the economic review of sharia, to describe the use of dead land in gampong leubok tilam kecamatan cot girek regency aceh north in sharia economic review, To answer this problem the authors use field research research type with qualitative research form with data collection in field then processed and analyzed with descriptive analysis then presented to answer the above problems. In addition, data collection from the field is then analyzed and grouped into primary and secondary data. The primary data is data that comes from the field of observation and interview. While the secondary data in the form of bibliographic data which includes books, other supporting books related to the issues being discussed. The result of the research is the utilization of dead land may even circumcision, but the implementation is still contradict between expectation with reality.